1996
DOI: 10.1007/bf00224560
|View full text |Cite
|
Sign up to set email alerts
|

RFLP analysis of resistance to Columbia root-knot nematode derived from Solanum bulbocastanum in a BC2 population

Abstract: The mapping of resistance toMeloidogyne chitwoodi derived from Solarium bulbocastanum is reported. A population suitable for mapping was developed as follows. A somatic hybrid of nematode-resistant S. bulbocastanum and cultivated tetraploid potato was produced. This was backcrossed to tetraploid potato, and a single resistant BC1 was selected and backcrossed again to the same recurrent tetraploid parent. The mapping population consisted of 64 BC2 progeny scored for restriction fragment length polymorphic (RFLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Recent cloning of this gene revealed that it encodes a member of the plant resistance protein family characterized by the presence of a putative nucleotide binding site and a leucine-rich repeat. Brown et al (1996) used QTL analysis confirmed supports a genetic model equivalent to monogenic dominant control.…”
Section: Discussionsupporting
confidence: 56%
“…Recent cloning of this gene revealed that it encodes a member of the plant resistance protein family characterized by the presence of a putative nucleotide binding site and a leucine-rich repeat. Brown et al (1996) used QTL analysis confirmed supports a genetic model equivalent to monogenic dominant control.…”
Section: Discussionsupporting
confidence: 56%
“…They were inherited in the dihaploid population where segregation was also detected. Isozyme and molecular markers may be usefully employed to follow and accelerate the introgression of traits of interest from S. aethiopicum into eggplant, as has been demonstrated in other Solanaceae (Brown et al 1996;Fulton et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…(5,6,18). Resistance to M. chitwoodi has been transferred from a resistant genotype of S. bulbocastanum to the gene pool of the cultivated potato by somatic hybridization (1,7), and a single gene has been localized on chromosome 11 that appears to control this resistance (8). Also, various levels of resistance to M. hapla have been reported (9,15,18).…”
mentioning
confidence: 99%